PROFIL INDUSTRI RUMAH TANGGA TAHU TEMPE â€œXâ€ DI KELURAHAN BAHU KECAMATAN MALALAYANG - Sinike ., Hara; Ribka M. Kumaat; Paulus A. Pangemanan; Mex L. Sondakh (Sam Ratulangi University, 2017)
This study aims to determine the profile of Tahu Tempe industry in Bahu District of Malalayang. This research was conducted for 3 months starting from preparation to reporting. Place of research in Bahu District of Malalayang. The data used are primary data and secondary data. Primary data were obtained through direct interviews with business owners using a questionnaire. Secondary data was obtained from Department of Industry (Dinas Perindustrian) of Manado City. Data were analyzed by using descriptive analysis where the data were presented in table and then discussed descriptively. The results showed that the industry of Tahu Tempe â€œXâ€ in Bahu District of Malalayang earned a profit of Rp14.661.667 per month. This profit is obtained by subtracting revenue of Rp59,250,000 per month with total cost of Rp44,588,333 per month.